Acute effects of cycling on running step length and step frequency - Gottschall, J. S.; Palmer, B. M. (The Journal of Strength and Conditioning Research, 2000)
This study determined the acute effects of an intense cycling bout on running kinematics (step length and step frequency) and on running performance (speed and efficiency). Ten male triathletes completed 2 sessions of testing on separate days. During the first session (the cycle/run condition), the participants completed a 30-minute high-intensity cycling bout, immediately followed by a 5-km run at race effort. For the second session (run/run condition), the participants completed a 30-minute high-intensity running bout at the heart rate measured during the cycling bout, immediately followed by a 5-km run at race effort. Analysis indicated that immediately following the cycling bout, the participants ran with a smaller step length (SL) and a higher step frequency (SF). However, as the cycle/run condition 5-km run progressed, the participants ran with increasing SL, decreasing SF, increasing speed, and increasing efficiency in comparison with the measurements of the run/run condition. Practically, measurements of running kinematics and running performance after cycling differed from measurements taken immediately after running. Therefore, the notion that running form differs after cycling is not merely an individual athlete`s perception, but a valid observation.